JUSTIFICATION OF THE ECONOMIC EXPEDIENCY OF ENERGY-SAVING TECHNOLOGIES INTRODUCTION IN THE REPUBLIC OF TATARSTAN WITH A VIEW OF THE RELIABILITY INCREASE OF THE HOUSING AND COMMUNAL SERVICES - G. M. Kvon (Russian Journal of Economics and Law)
The article views the economic aspects of heat supply system reconstruction with a view of increasing the efficiency of the housing and communal services system. The author presents the results of business plan aimed at justification of energy-saving equipment implementation.